Inclusive classroom – teaching multicultural groups of students – an intercultural project with students from 13 countries - Wilinkiewicz-Górniak, Lucyna (Scripta Neophilologica Posnaniensia, 2019)
Educating multicultural groups is not easy as a teacher has to deal with students from different cultural backgrounds in limited space and time. Still, it is feasible, provided that we are able to create a positive and trusting classroom environment in which all students are made to feel valued, respected and welcome. The one that combats stereotypes and prejudices allows multiple perspectives and ways of thinking and helps students develop a positive self-image. In such a classroom students can develop not only knowledge and skills, but also multicultural awareness, if only they are willing to coexist and cooperate with each other as well as accept and appreciate their varied backgrounds. Some points that I found to be the keys to success in my applied research are: culturally responsive teaching and differentiated instruction taking into account not only cultural diversity but also different learning styles and preferences. Apart from their flexibility in the area of methodology, a teacher should use a multisensory approach to appeal to different learning styles.